KEADILAN KONTRAKTUAL PADA PERJANJIAN BAKU DIGITAL DI PLATFORM SHOPEE: KLAUSULA SEPIHAK, AUTO-RENEWAL, DAN STANDAR ‘INFORMED CONSENT’ DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN - Dwi Putri Ariska; Zainal Said; Ade Alya; Akbar Akbar; Ardian Aras; Andi Megayanti (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze contractual justice in standard digital agreements on the Shopee platform, particularly regarding unilateral clauses, auto-renewal systems, and informed consent standards from a consumer protection perspective. This research employed a field research method using a qualitative and empirical juridical approach. Data were collected through observation, interviews, and documentation involving students of IAIN Parepare as active Shopee users. The findings indicate that Shopee’s digital standard agreements are still dominated by unilateral clauses that provide greater authority to business actors than consumers. In addition, the auto-renewal system in several services is not fully understood by users, potentially causing losses due to the lack of transparency in information delivery. The study also found that most users do not read or fully understand the terms and conditions before agreeing to use the service, indicating that the principle of informed consent has not been optimally implemented. Therefore, Shopee’s digital standard agreements have not fully reflected the principles of contractual justice and consumer protection. This study is expected to provide recommendations for business actors, consumers, and regulators in improving transparency and consumer protection in the digital era.